Diagnostics and loading of an atomic optical dipole trap - Brzozowski, Krzysztof; Krzemień, Leszek; Zachorowski, Jerzy; Gawlik, Wojciech (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We describe diagnostic techniques used for optimization of loading of an optical dipole trap with CO2 laser and 87Rb atoms. Atoms, precooled in a magneto-optical trap, were loaded into the trap formed by a weakly focused CO2 laser beam with the waist of about 150 μm and power of 50 W. In addition to determining the atom number and temperature, the effect of the loading geometry on the time evolution of trapped atoms is discussed. It is shown that a direct study of this evolution can be used for determining the trap frequencies.
Optica Applicata, Vol. 40, 2010, nr 3, s. 557-563
Keywords: optyka; cold atoms; atom trapping; optical dipole trap